"Thus Speaks Ishtar of Arbela" Prophecy in Israel, Assyria, and Egypt in the Neo-Assyrian Period - Atkinson, Jason; Barstad, Hans M.; Barstad, Hans; Becking, Bob; Crouch, C. L.; Gordon, Robert P.; Gordon, Robert P.; Hamborg, Graham; Hilber, John W.; Marlow, Hilary; Nissinen, Martti; Reimer, David J.; et al. (Penn State University Press, 2021)
Thus Speaks Ishtar is a collection of essays about prophets and prophecy in the ancient Near East during the "Neo-Assyrian Period." This was the time when some of Israel's greatest prophets emerged, and we also have from the same general period a number of prophetic texts found on the site of the ancient Assyrian city of Nineveh. The book examines the basic idea of prophecy and how this is shaped by the way we study the subject, and it then presents a number of fresh insights on a range of prophetic topics. These include the relationship between Israelite and other forms of prophecy in Assyria and Egypt and the relationship between what prophets said and the written forms in which their words were passed on. Other topics of contemporary interest include what these prophetic texts have to say about the environment, the place of intercession in Israelite and Assyrian religion, and whether the message of the trailblazing Israelite prophets of the eighth century was basically about judgment and community ruin or about hope and community well-being